Global, regional prevalence, incidence and risk factors of knee osteoarthritis in population-based studies. (December 2020) - Cui, Aiyong; Li, Huizi; Wang, Dawei; Zhong, Junlong; Chen, Yufeng; Lu, Huading
Abstract: Background: Knee osteoarthritis (OA) is a major cause of disability in the elderly, however, there are few studies to estimate the global prevalence, incidence, and risk factors of knee OA. Methods: For this study, we searched PUBMED, EMBASE and SCOPUS from inception to April 4, 2020, without language restriction. We identified eligible studies with information on the prevalence or incidence of knee OA in population-based observational studies and extracted data from published reports. We did random-effects meta-analysis to generate estimates. This study was registered with PROSPERO (CRD42020181035). Findings: Out of 9570 records identified, 88 studies with 10, 081, 952 participants were eligible for this study. The pooled global prevalence of knee OA was 16⋅0% (95% CI, 14⋅3%-17⋅8%) in individuals aged 15 and over and was 22⋅9% (95% CI, 19⋅8%-26⋅1%) in individuals aged 40 and over. Correspondingly, there are around 654⋅1 (95% CI, 565⋅6–745⋅6) million individuals (40 years and older) with knee OA in 2020 worldwide. The pooled global incidence of knee OA was 203 per 10, 000 person-years (95% CI, 106–331) in individuals aged 20 and over. Correspondingly, there are around annual 86⋅7 (95% CI, 45⋅3–141⋅3) million individuals (20 years and older) with incident knee OA in 2020 worldwide. The prevalence and incidence varied substantially between individual countries and increased with age. The ratios of prevalence and incidence in females and males were 1⋅69 (95% CI, 1⋅59–1⋅80, p <0⋅00) and 1⋅39 (95% CI, 1⋅24–1⋅56, p <0⋅00), respectively. Interpretation: Our study provides the global prevalence (16⋅0% [95% CI, 14⋅3%-17⋅8%]) and incidence (203 per 10, 000 person-years [95% CI, 106–331]) of knee OA. These findings can be used to better assess the global health burden of knee OA. Further prospective cohort studies are warranted to identify modifiable risk factors for providing effectively preventive strategies in the early stages of the disease. Funding: This work was supported by grants from the National Natural Science Foundation of China (nos. 81772384 and 81572174 ).